2019
DOI: 10.5222/buchd.2019.21704
|View full text |Cite
|
Sign up to set email alerts
|

Iron, Folate and Vitamin B12 Status of Children and Adolescents: Single Center Study in the Aegean Region

Abstract: Objective: Although anemia is frequently seen in children, there isn't adequate number of study related with this issue. In this study, we aimed to investigate iron, folate and vitamin B12 status in children and adolescents in a single center in the Aegean region of our country. Method: We retrospectively evaluated the children without chronic disease who were admitted to our hospital between 2008-2016 (n=7310). Ferritin, iron and iron binding capacity were measured by Olympus 2700 analyzer. Folate and vitamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…24,28,29 In a study conducted in Turkey, no significant difference was found between sex. 25 In our study, no significant difference was found between sex and vit B12 levels.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…24,28,29 In a study conducted in Turkey, no significant difference was found between sex. 25 In our study, no significant difference was found between sex and vit B12 levels.…”
Section: Discussioncontrasting
confidence: 61%
“…Considering the relationship between hematological parameters and vit B12 level, in the study conducted by Çolak et al, 25 no relationship was found between Hb, leukocyte count, platelet count and vit B12 levels. In our study, unlike the other study, a significant relationship was found between leukocyte and platelet counts and vit B12 level.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Çolak et al found the frequency of deficiency to be 16.9% in their study with 7310 children in Izmir. In this study, the lower limit of vitamin B12 was taken as 200 pg/ml (7). In another study conducted with a total of 889 participants aged 12-22 years in Diyarbakır, Turkey, the deficiency was found in 14.4% of the participants when the vitamin B12 cut-off level was taken to be 240 pg/ml (8).…”
Section: Discussionmentioning
confidence: 97%
“…19 In a study conducted in Turkey involving children aged 1-18 years, anemia was found at a rate of 18.8% and vitamin B12 deficiency at a rate of 16.9%. 20 As a result, it is not possible to link TLOC with anemia and vitamin B12 insufficiency.…”
Section: Discussionmentioning
confidence: 99%